Erratum: Association between alcohol consumption and rotator cuff tear. (2nd September 2016) - Passaretti, Daniele; Candela, Vittorio; Venditto, Teresa; Giannicola, Giuseppe; Gumina, Stefano
Abstract: Results — Total alcohol consumption, wine consumption, and duration of alcohol intake were higher in both men and women with RCT than in both men and women in the control group. Excessive alcohol consumption was found to be a risk factor for the occurrence of RCT in both sexes (men: OR =3.0, CI: 1.5–6.0, p < 0.001; women: OR =3.6, CI: 1.7–7.8, p < 0.001). Massive tears were associated with a higher intake of alcohol (especially wine) than smaller lesions.